The Use of Instagram Social Media for Religious Moderation among Students of the Faculty of Da’wah and Communication at UIN Alauddin Makassar - M. Alvishandi D; Arifuddin Tike; Kamaluddin Tajibu (Jurnal Mercusuar, 2023)
In the context of rapid social and technological changes, this research aims to delve into the impact of the intensity of Instagram social media usage on the patterns of moderate religious behavior among students of the Faculty of Da’wah and Communication at UIN Alauddin Makassar. This study seeks to understand how the existence of social media influences religious dimensions among students. The research methodology adopts a quantitative approach with an explanatory method to provide insights into the relationship between the intensity of Instagram social media usage (measured by frequency and duration of usage) and moderate religious behavior exhibited by students. The research was conducted at the Faculty of Da’wah and Communication at UIN Alauddin Makassar. The findings draw attention to two main aspects: Firstly, the prevalence of Instagram usage is quite high among students of the Faculty of Da’wah and Communication, with an average usage of 15-18 times a week and a duration of about 9-11 hours per week. Secondly, the findings provide an overview of the low level of moderate religious behavior, with only 46.5% of respondents showing behavior reflecting moderate religious attitudes. The analysis of the impact of Instagram social media usage on moderate religious behavior indicates that factors such as national commitment (X1), religious tolerance, anti-violence attitudes, and accommodation of local culture have varied effects. It is observed that religious tolerance has a significant influence, reaching 57%, while other variables have lower impacts. From this research, it can be concluded that awareness of the impact of Instagram social media usage on patterns of moderate religious behavior is important. Despite high social media usage intensity, additional efforts are needed to stimulate moderate religious behavior patterns among students of the Faculty of Da’wah and Communication. These findings are expected to provide valuable insights for policymakers, educators, and academics to formulate strategies that support the development of moderate religious behavior in an evolving digital era.